2006
DOI: 10.1128/jvi.00676-06
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Inhibits Neuronal Differentiation and Induces Apoptosis in Human Neural Precursor Cells

Abstract: Human cytomegalovirus (HCMV) is the most common cause of congenital infections in developed countries, with an incidence varying between 0.5 and 2.2% and consequences varying from asymptomatic infection to lethal conditions for the fetus. Infants that are asymptomatic at birth may still develop neurological sequelae, such as hearing loss and mental retardation, at a later age. Infection of neural stem and precursor cells by HCMV and consequent disruption of the proliferation, differentiation, and/or migration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
167
4
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 145 publications
(195 citation statements)
references
References 61 publications
18
167
4
6
Order By: Relevance
“…Nevertheless, the relevance of HCMV-induced differentiation in the context of CNS development and finding why it is reversed when viral concentration increases are a matter for further investigation. In contrast with our findings in SK-N-MC cells, previous reports showed a decrease in NPC differentiation to neurons and glia after HCMV infection (Odeberg et al 2006(Odeberg et al , 2007. Indeed, the experimental methods used in these studies were different, and since we did not induce differentiation, it occurred spontaneously.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, the relevance of HCMV-induced differentiation in the context of CNS development and finding why it is reversed when viral concentration increases are a matter for further investigation. In contrast with our findings in SK-N-MC cells, previous reports showed a decrease in NPC differentiation to neurons and glia after HCMV infection (Odeberg et al 2006(Odeberg et al , 2007. Indeed, the experimental methods used in these studies were different, and since we did not induce differentiation, it occurred spontaneously.…”
Section: Discussioncontrasting
confidence: 99%
“…The level of detection of viral particles in the cell lines used here was consistent with the results obtained using a different source of NPC (Luo et al 2008). However, it is dissimilar to those of others who have reported that NPCs are fully permissive to the infection, but few viral particles are released (Odeberg et al 2006). We observed that viral production in SK-N-MC was similar to the one in fibroblasts but not detectable in hNS-1.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These findings are in line with our previous results showing that HCMV infection of fetal neural progenitor inhibits their differentiation. 26 Other studies have suggested that halted differentiation of neuroprogenitor cells is an early step in gliomagenesis. 27 Since HCMV proteins and nucleotide sequences seem to be present in most GBMs 16,[28][29][30] and that HCMV-IE expression is a prognostic marker for poor patient survival irrespective of the GBM subtype, 18 our present model of HCMV infection of primary GBM cells appears to recapitulate early events during glioma development.…”
Section: Discussionmentioning
confidence: 99%